The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1361-6579/ac0fbd
|View full text |Cite
|
Sign up to set email alerts
|

Regions of interest selection and thermal imaging data analysis in sports and exercise science: a narrative review

Abstract: Objective: Infrared thermography (IRT) is a non-invasive, contactless and low-cost technology that allows recording of the radiating energy that is released from a body, providing an estimate of its superficial temperature. Thanks to the improvement of infrared thermal detectors, this technique is widely used in the biomedical field to monitor the skin temperature for different purposes (e.g. assessing circulatory diseases, psychophysiological state, affective computing). Particularly, in sports and exercise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 152 publications
0
8
0
Order By: Relevance
“…Hence, such a metric is sensitive to a cumulative effect of both exercise and the recovery phase, characterized by an initial vasoconstriction followed by a vasodilation, respectively [ 12 ]. However, the effectiveness of other metrics indicative of the skin temperature response to exercised limb, and of different statistical indices describing skin temperature distribution, should be further explored within the same experimental paradigm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, such a metric is sensitive to a cumulative effect of both exercise and the recovery phase, characterized by an initial vasoconstriction followed by a vasodilation, respectively [ 12 ]. However, the effectiveness of other metrics indicative of the skin temperature response to exercised limb, and of different statistical indices describing skin temperature distribution, should be further explored within the same experimental paradigm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current reports using infrared thermography during exercise have primarily focused on measuring absolute body temperature. However, these attempts have demonstrated limited effectiveness, and almost no significant correlations have been found with physiological parameters 1 , 14 . In the current study, we found no statistical changes in surface temperatures during the incremental exercise test.…”
Section: Discussionmentioning
confidence: 99%
“…When an IR image is captured, it does not differentiate between the region of interest (ROI) and the background. Various techniques have been used to capture the ROI, either manually or automatically, depending on the distance between the IR equipment and the participant (Barcelos et al, 2014;Quesada, 2017;Perpetuini et al, 2021). After obtaining the necessary images, qualitative and quantitative approaches are used for their interpretation.…”
Section: Introductionmentioning
confidence: 99%